Crystal chemistry of trialkylsilyl‐capped (3Z)‐4‐(methylthio)‐3‐penten‐1‐yne: polymorphism, twinning and ambiguity of order–disorder descriptions. Issue 5 (3rd October 2016) - Lumpi, Daniel; Kautny, Paul; Stöger, Berthold; Fröhlich, Johannes
Abstract : Silyl‐capped ene‐yne compounds crystallize in layers and feature polymorphism and twinning. Abstract : The crystallization behavior of trimethylsilyl‐capped (3 Z )‐4‐(methylthio)‐3‐penten‐1‐yne (1‐TMS) and the triisopropylsilyl and tert ‐butyldimethylsilyl analogues (1‐TIPS) and (1‐TBDMS) was investigated. (1‐TMS) crystallizes in the Sohncke space group P 21 21 21 with Z ′ = 1. (1‐TIPS) exists as two polymorphs, both crystallizing in with Z ′ = 2 independent molecules. Polymorph (I) is an order–disorder (OD) twin. Two interpretations in terms of M = 1 or M = 2 kinds of OD layers are possible, with different degrees of idealization. Polymorph (II) is fully ordered (non‐twinned). Its structure can be derived from polymorph (I) by inverting the orientation of every second molecule. (1‐TBDMS) (, Z ′ = 2) is an OD twin, where the OD description is unambiguously in M = 1 kinds of layers.